(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2023)
Yunis Varon Syndrome was first discovered by Emilio Yunis and Humberto Varon in the year 1980. It affects both genders in equal number. Most of the infants are with Cleidocranial dysplasia, ectodermal anomalities, distal aphalangia. By the characteristic features which including deformity of the pelvis, dislocation of hips , bone fracture, urinary tract abnormalities, central nervous system abnormalities by this they have reported the condition as Yunis Varon Syndrome. This is an autosomal recessive inherited multisystem disorder due to FIG4 gene mutations, consanguineous marriages, Lysosomal defects, which may leads to improper in the functioning of organs in the infants. Metabolic disorders in which abnormal growth due to some toxic substances in the body. Affected people with this syndrome may experience breathing problems, abnormalities in the skeletal system, congenital heart defects. Genetic testing for mutation can be detected through diagnosis. In some conditions they may also be detected before birth of the baby that is prenatally by ultrasonography.Many of the infants did not survive beyond on year. Genetic counselling will be of benefit for affected individuals and their families.